Humanitarian intervention and the responsibility to protect : who should intervene? - Pattison, James , 1980- (Oxford University Press, 2010)
This book considers who should undertake humanitarian intervention in response to an ongoing or impending humanitarian crisis. It develops a normative account of legitimacy to assess not only current interveners, but also the desirability of potential reforms to the mechanisms and agents of humanitarian intervention